SPECIFIC CHARACTERISTICS OF THE ACCOUNT OF FIXED VEHICLES IN AUTOMOBILE TRANSPORT ENTERPRISES (International Congress on Economics, Management and Business Studies, 2026)
The article researches the scientific-methodical basis of development of network working accounting plan and improvement of fixed assets accounting for motor transport enterprises.
Keywords: Automobile transport, working account plan, depreciation, mileage method, IAS 16, IAS 36, revaluation model, segment report, analytical subaccount, network-specialized methodology.